Helping Low Vision Patients to Read Again - Salmon, Don (Canadian Journal of Optometry, 1982)
Rehabilitation of the low vision patient is both optical and psychological. This paper purposely neglects the optical consideration in order to stress the human management aspect of rehabilitation.